An evaluation of impacts in “Nanoscience & nanotechnology”: steps towards standards for citation analysis - Leydesdorff, Loet (Scientometrics, 2013)
One is inclined to conceptualize impact in terms of citations per publication, and thus as an average. However, citation distributions are skewed, and the average has the disadvantage that the number of publications is used in the denominator. Using hundred percentiles, one can integrate the normalized citation curve and develop an indicator that can be compared across document sets because percentile ranks are defined at the article level. I apply this indicator to the set of 58 journals in the WoS Subject Category of “Nanoscience & nanotechnology,” and rank journals, countries, cities, and institutes using non-parametric statistics. The significance levels of results can thus be indicated. The results are first compared with the ISI-impact factors, but this Integrated Impact Indicator (I3) can be used with any set downloaded from the ( Social ) Science Citation Index . The software is made publicly available at the Internet. Visualization techniques are also specified for evaluation by positioning institutes on Google Map overlays.